Two new species within the genus Seira Lubbock, 1869 from Morocco (Collembola, Entomobryidae) - Negri, Ilaria; Pellecchia, Marco; Fanciulli, Pietro Paolo (Zootaxa, 2005)
Two new species of the genus Seira are described: Seira atlantica n. sp. and Seira maroccana n. sp. They come from two different sites along the Atlas mountains (Morocco); their descriptions are mainly based on the distribution and number of the dorsal macrochaetae and pigmentation. Both new taxa belong to the domestica group of species, characterized by a reduced number of dorsal macrochaetae. Their relationships among congeneric species are discussed.